Efficacy of robust optimization plan with partial‐arc VMAT for photon volumetric‐modulated arc therapy: A phantom study - Miura, Hideharu (J Appl Clin Med Phys, 2017)
This study investigated position dependence in planning target volume (PTV)‐based and robust optimization plans using full‐arc and partial‐arc volumetric modulated arc therapy (VMAT). The gantry angles at the periphery, intermediate, and center CTV positions were 181°–180° (full‐arc VMAT) and 181°–360° (partial‐arc VMAT). A PTV‐based optimization plan was defined by 5 mm margin expansion of the CTV to a PTV volume, on which the dose constraints were applied. The robust optimization plan consisted of a directly optimized dose to the CTV under a maximum‐uncertainties setup of 5 mm. The prescription dose was normalized to the CTV D(99%) (the minimum relative dose that covers 99% of the volume of the CTV) as an original plan. The isocenter was rigidly shifted at 1 mm intervals in the anterior‐posterior (A‐P), superior‐inferior (S‐I), and right‐left (R‐L) directions from the original position to the maximum‐uncertainties setup of 5 mm in the original plan, yielding recalculated dose distributions. It was found that for the intermediate and center positions, the uncertainties in the D(99%) doses to the CTV for all directions did not significantly differ when comparing the PTV‐based and robust optimization plans (P > 0.05). For the periphery position, uncertainties in the D(99%) doses to the CTV in the R‐L direction for the robust optimization plan were found to be lower than those in the PTV‐based optimization plan (P < 0.05). Our study demonstrated that a robust optimization plan's efficacy using partial‐arc VMAT depends on the periphery CTV position.